Inflatable multichannel rectal applicator for adaptive image-guided endoluminal high-dose-rate rectal brachytherapy: design, dosimetric characteristics, and first clinical experiences - Schmid, Maximilian P.; Berger, Daniel; Heilmann, Martin; Bör, Jessica; Wisgrill, Bernd; Azizi-Semrad, Ursula; Nesvacil, Nicole; Pötter, Richard; Kirisits, Christian; Schmid, Rainer (Journal of Contemporary Brachytherapy, 2017)
Purpose: To investigate the dosimetric results and first clinical experiences with a new designed balloon applicator with adjustable catheters for endoluminal brachytherapy for patients with locally advanced rectal cancer not undergoing surgery. Material and methods: The applicator consists of an inflatable rectal balloon with six attached Foley catheters used as guidance for the inserted brachytherapy plastic needles. The construction of the applicator and the dosimetric profile in terms of representative dose points in 0, 2, 5, 10 mm ipsilaterally and in 0 mm contralaterally are described. The first clinical outcomes in three patients are reported. Results: For all three patients, a reproducible dose gradient was achieved. The surface dose on the target side was 204 ± 19% of the normalized dose in 5 mm (100%) tissue depth, and 143 ± 8% in 2 mm and 64 ± 3% in 10 mm tissue depth, while the surface dose on the contra-lateral side was 20 ± 8%. After radiochemotherapy with 50 Gy external beam radiotherapy and concomitant administration of capecitabine, a HDR brachytherapy boost in 2-3 fractions of 7-10 Gy each was delivered. All patients achieved a clinical complete response 3 month after the treatment, and no major toxicity was observed. Conclusion: The use of the applicator was clinically feasible, and resulted in a stable and reproducible dose distribution. First clinical results are promising.